2020
DOI: 10.1002/berj.3626
|View full text |Cite
|
Sign up to set email alerts
|

Education research and educational practice: The qualities of a close relationship

Abstract: The relationship between education practice and education theory has a long history. In modern times, education practice and its relation to education research has been central to debates about the nature and quality of education as an academic discipline in universities. This paper reports an empirical study that investigated a new instantiation of the practice-theory debates -'close-to-practice' research in education. The research, a) sought to define and further articulate the concept of close-to-practice r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 13 publications
0
52
0
Order By: Relevance
“…Biesta, 2007;Thomas, 2012) and yet there is little or no critical reflection on these central arguments. In agreement with Hordern's (2020) critique of Wyse et al (2018Wyse et al ( , 2020, there is an overly dichotomised view of research and practice that characterises the work, which undermines and misrepresents the breadth and depth of research in this field of inquiry.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Biesta, 2007;Thomas, 2012) and yet there is little or no critical reflection on these central arguments. In agreement with Hordern's (2020) critique of Wyse et al (2018Wyse et al ( , 2020, there is an overly dichotomised view of research and practice that characterises the work, which undermines and misrepresents the breadth and depth of research in this field of inquiry.…”
Section: Introductionmentioning
confidence: 82%
“…knowledge emerges from the conjoined understandings of teachers and others committed to long-term, highly systematic observation and documentation of learners and their sense making'. Indeed, Wyse et al (2018Wyse et al ( , 2020 acknowledge the importance of collaboration between research and practice and include 'collaborative work' in their definition of CtP research, but then leave this important aspect underexplored. This is despite the authors citing feedback from the Research Excellence Framework (REF) 2014 Education sub-panel, which indicated that some papers from the REF '.…”
Section: Wherein the Collaboration?mentioning
confidence: 99%
See 1 more Smart Citation
“…Our aim was not to prescribe specific scholarly agendas but rather to provide guidelines for reporting research in the journals we manage. Our effort was occasioned by the 2018 publication of the APA guidelines, the SRCD’s adoption of a sociocultural policy for their journals in 2020, and similar reports issued internationally (e.g., by the British Educational Research Association; see Wyse et al, 2018). As these guidelines are already circulating in academic communities that intersect with ours, it seemed appropriate to examine their implications for authors seeking to publish in the JOREL, JOEE, JAEOL, and JEE, and also for reviewers and consumers of research in these outlets.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore thought it would be more efficient to compose one document that provides greater continuity and clarity of expectations for scholars across leading outlets in our field(s). Second, although the guidelines referenced in this essay emanate from associations based largely in the United States, they are aligned with best practices that are currently advocated worldwide (e.g., Wyse et al, 2018). We therefore thought it beneficial to compose a document jointly to ensure any proposed guidelines were not overly restrictive or too narrowly tailored.…”
Section: Summary Of Recently Published Guidelines By the Aera Srcd mentioning
confidence: 99%